Performance comparison of Rabin-P and RSAOaEP encryption scheme in securing data on cloud - Saiful Azam, Saifaris Azizi; Syed Adnan, Syed Farid; Asbullah, Muhammad Asyraf (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper analyses the Rabin-p encryption scheme on the cloud in terms of runtime on VMware and Amazon Web Services. Amazon provides a comprehensive cloud computing platform called Amazon Web Services (AWS). It provides diverse cloud services, including computing power, storage options, and databases. Therefore, Rabin-p is introduced to Amazon Web Services. The encryption and decryption runtimes and the runtime when uploading ciphertext to AWS have been analyzed. Rabin-p is an asymmetric method that provides increased security. This can help to improve cloud security for both AWS and its clients. The length of primes significantly impacts the speed of encryption and decryption processes, generally resulting in longer processing times for longer primes. In comparative tests across various prime lengths, Rabin-p demonstrated faster encryption and decryption speeds when compared to RSA-OAEP. Specifically, Rabin-p consistently exhibited lower encryption times than RSA-OAEP at prime lengths of 341, 682, and 1365 bits at almost 50% faster but Rabin-p runtime increased while upload and download to the cloud. This suggests that Rabin-p may offer greater efficiency for data at rest.